External labor migration in the Russian Federation - Pavel A. Smelov; Elena A. Egorova (Статистика и экономика)
Purpose of the study. A problem of assessing international labor migration in the past twenty years is a very topical issue in many countries around the world. The main problem of the study of labor migration is the lack of full and reliable information about this phenomenon. The main objective of this study is to assess the possibility of statistical assessment of external labor migration in the Russian Federation.Materials and methods. The article provides an overview of the international basic documents in the field of the organization of labor statistics of migrants, and also defines the concepts of labor migration and foreign employees from the point of view of international and Russian legislation. The sources of information were the data of the summary information on migration records of the Ministry of Internal Affairs of the Russian Federation, as well as microdata on the form 5-PERSONAL INCOME TAX of the Federal Tax Service of Russia. The main methods, used in the study are: methods of analysis and synthesis, methods of data measuring and aggregating, methods of working with microdata, analytical indicators of the dynamics, graphical and tabular method.Results and conclusion. Based on the study, several conclusions can be drawn. First, in the Russian Federation there are objective administrative sources of data on legal external labor migrants. Secondly, these sources are not harmonized and it is necessary to carry out methodological work on the harmonization of data and the construction of time series on the number of external labor migrants. Also, these services need to provide access to their information system to the Federal State Statistics Service to compile data on external labor migrants in various socio-demographic sections. Third, then the legal external labor migration to the Russian Federation increases every year and in 2017 amounted to about 108 million people, the main source countries are post-Soviet countries, and the high-ranking subjects of attraction are the cities of Moscow, St. Petersburg and Moscow Region.